Do Turkish reimbursement recommendations cover current European Lipid Guidelines? A retrospective analysis of patients presenting with first acute coronary syndrome - Deniz Demirci; Duygu Ersan Demirci; Murat Esin; Özkan Kayhan; Şakir Arslan (KARE Publishing, 2017)
Objective: This study was a comparison of the statin therapy protocol issued by the European Society of Cardiology (ESC) and the Ministry of Health's Health Implementation Directive (SUT) in Turkey, performed in order to assess the adequacy of hyperlipidemia treatment indications for primary prevention. Methods: A total of 582 patients with first acute coronary syndrome were included in the study. Patients with noncritical stenosis observed on coronary angiography or a history of atherosclerotic disease were excluded. The risk calculation was determined using age, sex, smoking status, presence of diabetes mellitus, total cholesterol, and lipoprotein levels. Statin treatment indications were evaluated according to the ESC guidelines (2016) and the SUT (2016). Results: Statin treatment was indicated for 96% of diabetic patients, and according to the ESC, it was appropriate for 13.5% of nondiabetic patients, while the SUT recommendation included 13.3% of nondiabetic patients (p<0.05). For patients younger than 60 years of age, the SUT had more guidelines than the ESC; however, for patients aged 70 to 90, the ESC had more guidelines than the SUT. For patients over 90, the indications were the same. For patients with low-density lipoprotein-cholesterol (LDL-C) >190 mg/dL there was greater discrepancy between the SUT and ESC guidelines. According to the SUT, all patients >190 mg/dL are to receive treatment. The ESC had more guidelines than the SUT for cases of LDL-C <160 mg/dL. Conclusion: The scope of the SUT guidelines is generally not narrower than the ESC indications. However, the indications for patients >60 years of age and those with LDL-C >160 mg/dL should be reassessed, as they are more limited than those of the ESC. A new treatment algorithm should be defined.